Planning and implementing sustainability in higher education institutions: an overview of the difficulties and potentials - Leal Filho, W.; Pallant, E.; Enete, A.; Richter, B.; Brandli, L. L. (International journal of sustainable development and world ecology, 2018)
Planning in sustainable development is believed to be an important element in allowing higher education institutions to set their goals and to commit themselves towards undertaking concrete actions and measures at all levels in order to implement sustainability. Yet, there is a paucity of research that has looked at the extent to which planning can support institutions of higher education to assess their performances and to determine whether the set aims have been met. This research gap needs to be met to allow a better understanding of how planning can help to promote the integration of the three components of sustainable development - economic development, social development and environmental protection in higher education. This paper explores the challenges for planning the sustainable development in higher education, also outlining the potentials lessons learned that could assist in improving Education for Sustainable Development efforts in Higher Education Institutions. Among its main results are the fact that many universities wish to pursue sustainable development, but their efforts are hindered by lack of institutional support and planning and limited emphasis on approaches, such as problem-based learning. The universities that are engaged in the field have to face many problems, varying from limited resources to lack of trained staff. As a result, integrated approaches to sustainability become difficult to implement. Finally, the paper has identified the fact that many opportunities offered mainstream developments, such as the UN Declaration 'The World we Want' or the UN Sustainable Development Goals are not being put to full use.